L’idée de pédagogie scientifique chez Freinet - Baptiste Jacomino (Recherches en Éducation)
We find in Freinet’s work a radical critic of science. But he also defends a scientific pedagogy. This scientific pedagogy is not condemned because it would be free from all the impasses in which science was locked. Freinet imagines an intuitive science which would be able to grasp the movement of life and to perfectly direct the action of the teacher. This idea hides the fact that the lack of knowledge is constitutive of any teaching situation. But even if he masks this epistemological specificity of pedagogy, Freinet offers teaching techniques that allow to tackle this lack of knowledge and are a possible alternative to the impasses in which the idea of ‌scientific pedagogy leads us.